Effects Of Essential Oil From Drypetes gossweileri S. Moore Stem Barks On Cell Release And Dna Synthesis Of Mycobacterium tuberculosis: Effects of essentail oil - MONI, Esther Del Florence NDEDI; NYEGUE, Maximilienne Ascension; ASSAM, Jean Paul ASSAM; BETOTE, Patrick Hervé DIBOUE; FEUDJIEU, Gaizirène EGOUME; PENLAP, Véronique BENG; ETOA, François-Xavier (Journal of Drug Delivery and Therapeutics, 2019)
Background: In the recent years, the proliferation of multi-drug-resistant and extensively drug-resistant strain to tuberculosis (TB) suggest that efforts are required to find alternative treatments. The designed study aimed to show the effects of essential oils (EO) from Drypetes gossweileri stem barks on Mycobacterium tuberculosis cell membrane release and DNA synthesis. Methods: The minimal inhibitory concentration (MIC) and minimal bactericidal concentration (MBC) were determined against two clinical isolates (IS53 and IS310) and the reference strain H37Rv ATCC 27294 using microdilution method. The effect of essential oil on cell membrane release of Mycobacterium tuberculosis was evaluated by measuring DNA, RNA and proteins release in extracellular medium using NanoDrop 1000 spectrophotometer to show the membrane integrity lose. The effect on DNA was performed by measuring genomic DNA and amplicons of MIRU 04 sequence produced when treated at MICs and MBCs concentrations to put in evidence the inhibitory effect of EO during DNA synthesis. Results: The results revealed that EO from Drypetes gossweileri stem barks exhibited strong activity with MIC ranging from 4.88 µg/mL against H37Rv and IS310 to 9.76 µg/mL against IS53. The significant release of DNA, RNA and proteins in extracellular medium were observed for treated cells at MIC and MBC concentrations compare to untreated cells. The most quantified biomolecules were proteins with concentration ranging from 370.9 104 ng/µL to 10630.0 104 ng/µL released at MIC concentration which increased from 1890.0 104 ng/µL to 12000.9 104 ng/µL at MBC. The inhibitory effect of DNA synthesis by EOs enhanced lower quantity of DNA for all treated cells at MIC and MBC compare to untreated cells. The results obtained in this study enabled the identification of two cellular targets (cell membrane and DNA) of EO from D. gossweileri stem barks on M. tuberculosis.